Generation, control and erasure of dual LIPSS in germanium with fs and ns laser pulses. (11th September 2020) - Casquero, Noemi; Fuentes-Edfuf, Yasser; Zazo, Raul; Solis, Javier; Siegel, Jan
Abstract: Laser-induced periodic surface structures (LIPSS) can readily be fabricated in virtually all types of materials and benefit from an efficient parallel patterning strategy that exploits self-organization. The wide range of different LIPSS types with different spatial scales and symmetries is continuously growing, addressing numerous of applications. Here, we report on the formation of two fundamentally different types of LIPSS on germanium upon exposure to femtosecond laser pulses (λ = 800 nm, 130 fs), featuring different periods and orthogonal orientations. On the one hand, the well-known low-spatial frequency LIPSS (LSFL) with a period ≍ λ and perpendicular orientation to the laser polarization are formed, which can be extended homogeneously in 2D by sample scanning. Additionally, extremely smooth ripples with a period ≍λ/2 and parallel orientation were generated at lower pulse numbers. We show that this new kind of ripples, named parallel high-spatial frequency LIPSS (HSFL-∥), can be superimposed onto LSFL by increasing the pulse number, forming complex dual LIPSS with nanohill-like morphology. While exposure to multiple nanosecond laser pulses is found to trigger also the formation of LSFL, HSFL-∥ cannot be formed under these conditions, which points out the role of ultrafast excitation in the formation of the latter. By performing time-resolved reflectivity measurements, we are able to resolve the melting and solidification dynamics, revealing melting of a very shallow surface layer (<20 nm) and melt durations of a few ns for both pulse durations pulses at the fluences employed for LIPSS formation. Finally, we demonstrate erasure of both types of LIPSS by exposure to single nanosecond pulses at high fluences, which paves the way for erasable multi-level data storage.